AB0639 Bone Mineral Density Is Decreased in Patients with Systemic Sclerosis and Correlates with Serum Ipth Levels: A Cross Sectional Study. (15th July 2016) - Sharma, S.K.; Sharma, S.K.
Abstract : Background: Systemic sclerosis is a multisystemic disease with devastating consequences. It is believed that osteoporosis is common in systemic sclerosis with causation being ascribed to the altered GI motility, malabsorption, immobility, use of glucocorticoids among other factors. A few studies have looked at osteoporosis and associated factors in patients with systemic sclerosis, however results are conflicting [1–2]. Objectives: The aim was to study the bone mineral density (BMD) in patients with systemic sclerosis and its correlation with organ involvement. Methods: Patients attending the Rheumatology Clinic at PGIMER, Chandigarh were screened and 100 patients meeting the American College of Rheumatology (ACR) criteria for systemic sclerosis were recruited for the study. In all such patients, BMD was measured using dual energy xray absorptiometry (DXA). Serum Vitamin D and iPTH levels were estimated. Results: Most of the participants were females (8:1). The mean age of the participants was 42±12 years. The median disease duration prior to recruitment was 5 years (3–8 years). Thirty four of eighty nine women were post menopausal at the time of conducting the study. 48% of patients had interstitial lung disease while 18% had pulmonary arterial hypertension. 56% had received corticosteroids while 16% had received cyclophosphamide. Most patient received 7.5 mg of corticosteroids intitially and the dose was tapered to 5mg once a day and then to alternate days and subsequently was stopped. Cyclophosphamide was given as a monthly pulse for 6 months when indicated. Among patients included, 72% of patients had a low bone mass at the spine while 42% had a low bone mass at the femoral neck. In all, 28% had osteoporosis of the lumbar spine while 6% had osteoporosis of the femoral neck. 41 patients exhibited hypocalcemia. Serum iPTH levels were elevated with a median value of 76.24 (50.26–102.675) pg/ml. Serum iPTH correlated inversely with low bone mass at the hip (p=0.023, r 2 =0121). We did not find a correlation with increasing age, postmenopausal status, low BMI, corticosteroid use, serum 25(OH) Vitamin D levels, disease duration, presence of ILD or PAH. Conclusions: Low bone mass is highly prevalent in patients with systemic sclerosis and correlates inversely with Serum iPTH levels. Serum iPTH levels may be an important marker for early diagnosis of osteoporosis in these patients and may help in timely institution of anti resorptive measures, hopefully, before the occurrence of fragility fractures References: Mok CC, Chan PT, Chan KL, Ma KM. Prevalence and risk factors of low bone mineral density in Chinese patients with systemic sclerosis: a case-control study. Rheumatology (Oxford). 2013 Feb; 52(2):296–303. Omair MA, Pagnoux C, McDonald-Blumer H, Johnson SR. Low bone density in systemic sclerosis. A systematic review. J Rheumatol. 2013 Nov; 40(11):1881–90. Disclosure of Interest: None declared